PELATIHAN PEMBUATAN POLA MENGGUNAKAN 3D PRINTING UNTUK PRAKTIKUM PENGECORAN DI SMK MUHAMMADIYAH 1 BANTUL - Arya Yusuf; Arianto Leman Soemowidagdo; Fredy Surahmanto; Joni Tri Setyawan; Siti Nursipa Wulida (LP2M Universitas Ibrahimy, 2024)
Vocational High Schools (SMK) act as key partners for higher education institutions, focusing on transferring knowledge and technology to the broader community. SMKs require high-level competencies for their teachers and students to meet the demands of today’s workforce effectively. To support this need, a community service program aimed at creating metal casting patterns was launched. This initiative called the off-campus community service activity (PkM DLK), was organized by a team of lecturers and students from the Department of Mechanical Engineering Education at Yogyakarta State University. The primary goal of this program was to train teachers and educational staff to proficiently create casting patterns using 3D printing technology, allowing for a more efficient and streamlined process. The activity was conducted at SMK Muhammadiyah 1 Bantul, involving both the university team and the school's teachers and staff, specially for the mechanical engineering program. The methodology used for this program was Participatory Action Research (PAR), which encouraged active participation from all involved. Key stages included an introduction to the program, hands-on practice designing pattern models using Inventor CAD 2024 software, simulating the printing process with Ultimaker Cura software, operating 3D printers, printing and finishing the patterns, and finally conducting a casting trial using the newly created patterns. Feedback was overwhelmingly positive, with participants giving an average score of 85.88, indicating a